Gas adsoprtion phenomenon in microporous zeolite adsorbent - Kamarudin, Khairul Sozana Nor; Chieng, Yu Yuan; Hamdan, Halimaton; Mat, Hanapi (2005)
Gas adsorption on zeolites gains remarkable attention in this new era of nanotechnology since it has industrial importance in many process industries. Efforts of chemists during the past few decades have advanced the field of synthesis and accelerated the development of zeolites with different physicochemical properties for specific application. New technologies involving gas separation, gas purification, gas storage, high temperature gas sensor, semiconductor material hold a great promise for industrial applications. In order to develop and design an efficient and economically feasible industrial adsorption process, it is important to understand the adsorption phenomena between solid and gas phases. The presence of metal cations in the extra-framework structure determines the accessibility of gas molecules into the zeolite framework. In addition, the selectivity and capacity of adsorption is also being influenced by the adsorbate-adsorbent interactions. The molecules may interact through dispersion, induction, field-quadrapole and/or repulsion forces. Hence, information on physicochemical properties of zeolites as well as the properties of adsorbent is equally important in order to understand gas adsorption phenomena in zeolite microstructures. Results of this study show that structural properties and adsorbate-adsorbent interactions affect gas adsorptive characteristics of zeolites.